Phytochemical Screening, Polyphenols Content, Antioxidant Power, and Antibacterial Activity of Herniaria hirsuta from Morocco - Kenza Ammor; Dalila Bousta; Sanae Jennan; Bahia Bennani; Abdellah Chaqroune; Fatima Mahjoubi (The Scientific World Journal)
The aim of this study is to investigate in vitro antioxidant and antibacterial activities of the aqueous and hydroethanolic extracts for aerial parts of Herniaria hirsuta. Extracts were screened for their possible antioxidant activities by three tests: DPPH free radical-scavenging, reducing power, and molybdenum systems. The screening of antibacterial activity of extracts was individually evaluated against sixteen bacteria species using a disc diffusion method. Flavonoids, total phenols, and tannins content were performed for both extracts. It shows higher content in the hydroethanolic extract. The hydroethanolic extract showed a significant antioxidant activity for the three methods studies to the aqueous extract, but nonsignificant results compared to the reference (BHT). However, both extracts have negative effect on the strains studies for the antibacterial activity.